Bioenergetic consequences of sex-specific mitochondrial DNA evolution. Issue 1957 (25th August 2021) - Bettinazzi, Stefano; Milani, Liliana; Blier, Pierre U.; Breton, Sophie
Abstract : Doubly uniparental inheritance (DUI) represents a notable exception to the general rule of strict maternal inheritance (SMI) of mitochondria in metazoans. This system entails the coexistence of two mitochondrial lineages (F- and M-type) transmitted separately through oocytes and sperm, thence providing an unprecedented opportunity for the mitochondrial genome to evolve adaptively for male functions. In this study, we explored the impact of a sex-specific mitochondrial evolution upon gamete bioenergetics of DUI and SMI bivalve species, comparing the activity of key enzymes of glycolysis, fermentation, fatty acid metabolism, tricarboxylic acid cycle, oxidative phosphorylation and antioxidant metabolism. Our findings suggest reorganized bioenergetic pathways in DUI gametes compared to SMI gametes. This generally results in a decreased enzymatic capacity in DUI sperm with respect to DUI oocytes, a limitation especially prominent at the terminus of the electron transport system. This bioenergetic remodelling fits a reproductive strategy that does not require high energy input and could potentially link with the preservation of the paternally transmitted mitochondrial genome in DUI species. Whether this phenotype may derive from positive or relaxed selection acting on DUI sperm is still uncertain.